MODELING THE DYNAMIC OF KALARE CRIME IN GOMBE METROPOLIS - AYUBA, SANDA; IBRAHIM, ADAMU; AJIYA, YAHAYA; ISHAKU, ADAMU; GARBA, IBRAHIM; ABUBAKAR, ALIYU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
The activities of kalare youth group have put an end to the lives of several innocent people of Gombe, the state capital of Gombe, Nigeria more than any other kind of crime in the recent history of the state. In this paper, a mathematical model of kalare crime with two categories of susceptible class was developed and analyzed. We obtained the existence and uniqueness of solution of the model equations, the basic reproduction number 0R best on the modification of the work of Umar (2013). The analysis shows the crime-free equilibrium is locally asymptotically stable whenever the threshold 0 1 R  and unstable if 0 1 R  . The crime present equilibrium of the model exists and it is found to be unique under certain condition. The numerical simulation carried on three different scenarios as R0 = 0.27714 1, 0 R = 0.20123 1and 0 R = 0.0694 1which shows that kalare crime can be drastically reduce.